2013
DOI: 10.1037/a0031958
|View full text |Cite
|
Sign up to set email alerts
|

Successful talent development in soccer: The characteristics of the environment.

Abstract: The holistic ecological approach to research in talent development in sport highlights the central role of the overall environment, as it affects an athlete in his or her athletic development. Applying the holistic ecological approach, this article examines talent development among male under-17 soccer players in a Danish soccer club with a history of successfully developing several of its juniors to top-level soccer players. Principal methods of data collection include interviews, participant observations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 33 publications
5
111
1
2
Order By: Relevance
“…Th e identifi ed players, especially by top-level clubs, are given obvious advantages in this selection system (Ashworth & Heyndels, 2007) even though there are many obstacles in this process (Larsen, Alfermann, Henriksen, & Christensen, 2013). Th ese environments are oft en characterized by high expectations, which might indicate that players may experience considerable personal pressure, especially from coaches.…”
Section: Characteristics Of Professional and Non-professional Footbalmentioning
confidence: 99%
“…Th e identifi ed players, especially by top-level clubs, are given obvious advantages in this selection system (Ashworth & Heyndels, 2007) even though there are many obstacles in this process (Larsen, Alfermann, Henriksen, & Christensen, 2013). Th ese environments are oft en characterized by high expectations, which might indicate that players may experience considerable personal pressure, especially from coaches.…”
Section: Characteristics Of Professional and Non-professional Footbalmentioning
confidence: 99%
“…Furthermore, athletes' experiences may vary depending upon the exigencies of the sporting environment and culture in which they operate. Previous research (e.g., Larsen, Alfermann, Henriksen & Christensen, 2013) has suggested that the environment in which athletes function is primarily a function of the relationship between players and support staff (e.g., coaches, assistants, and managers). These relationships are also driven by the organizational values.…”
Section: Within-career Transitions In Sportmentioning
confidence: 99%
“…Moreover the tale provides in-depth insight into goal setting processes and how applied sport psychology is practiced. Additionally the section underlines once again that sport psychology delivery is social constructed and thus the SPC and the player are key to success as well as considering that the program is interrelated and affected by the talent development environment (Henriksen et al, 2011;Larsen et al, 2013). Gilbourne and Richardson (2006) paper on tales from the field in professional football similarly describes the provision of sport psychology from a personal perspective thus supporting the need for first person perspectives in order to describe the process of doing sport psychology.…”
Section: The Art Of Goal Settingmentioning
confidence: 99%
“…Nevertheless, research so far has concluded, that the use of psychological strategies is difficult for clubs and players to integrate (Johnson et al, 2011;Larsen et al, 2012). In a case study made in a professional football club, the results showed that the players had difficulty in making their individual goal setting effective, which could indicate a lack of organization, knowledge or proficiency in the area (Larsen, Alfermann, Henriksen & Christensen, 2013). We are familiar with the fact that a thorough integration of goal setting strategy has a beneficial effect on performance.…”
mentioning
confidence: 99%